PENERAPAN METODE PEMBELAJARAN TWO STAY TWO STRAY UNTUK KETERAMPILAN MENYIMAK SISWA KELAS XI IPS SMAN 2 SIDOARJO - Ananda Berliana, Dinny (LATERNE, 2017)
Listening ist one of the language skills that have an important role to play with other language skills. But in fact, teaching listening skills is less liked by students because it is considered boring. The implementation of the Two Stay Two Stray method was chosen as one of the innovation to help students in learning and listen to the German language. This method in its implementation requires students to listen to the information that they obtained. As for the formulation of problem in this research is “How to apply  learning method Two Stay Two Stray for listening skill of German language to student of class XI IPS SMAN 2 Sidoarjo” with theme of Family (die Familie). The goal that writer wanted to achieve in this research is to describe the learning process of students in learning using method of Two Stay Two Stray especially in listening skill of German language in grade XI IPS SMAN 2 Sidoarjo with theme of Family (die Familie). In this qualitative work, writer is using a descriptive research. Data in this study were obtained from research instruments. Instrument in this research is observation sheet of student activity. Observation sheet used to observe the student activity during the learning process. This study was conducted in four meetings. The data which obtained were analyzed by using qualitative descriptive approach. The results showed that student activity in learning German language listening skills improved after the implementation of Two Stay Two Stray learning method. From the above information can be conclude this method can be an innovation so that students are more active in learning. Keyword: Learning Method, Two Stay Two Stray, listening skills